Deficit irrigation in grapevine improves water-use efficiency while controlling vigour and production quality - Chaves, Maria Manuela (2012)
Grapevine irrigation is becoming an important practice to guarantee wine quality or even plant survival in regions affected by seasonal drought. Nevertheless, irrigation has to be controlled to optimise source to sink balance and avoid excessive vigour. The results we present here in two grapevine varieties (Moscatel and Castela ˜o) during 3 years, indicate thatwe can decrease the amount ofwater applied by 50%(as in deficit irrigation, DI, and in partial root drying, PRD) in relation to full crop’s evapotranspiration (ETc) [full irrigated (FI) vines] with no negative effects on production and even get some gains of quality (in the case of PRD).We report that in non-irrigated and in several cases in PRD vines exhibit higher concentrations of berry skin anthocyanins and total phenols than those presented by DI and FI vines.We showed that these effects on quality weremediated by a reduction in vigour, leading to an increase on light interception in the cluster zone. Because plant water status during most of the dates along the season was not significantly different between PRD and DI, and when different, PRD even exhibited a higher leaf water potential than DI vines, we conclude that growth inhibition in PRD was not a result of a hydraulic control. The gain in crop water use in DI and PRD was accompanied by an increase of the δ13 C values in the berries in DI and PRD as compared to FI, suggesting that we can use this methodology to assess the integrated water-use efficiency over the growing season.